Inventions and institutions: Artistic research as a medium of change - Kirkkopelto, Esa (Peripeti, 2021)
During the irst decade of the new millennium, artistic research has secured its position as an acknowledged mode of academic research. Both among its practitioners and administrators, it has been understood rather as an independent research ield than as a particular research method. Artistic research may proceed according to many methods as well as create methods of its own. Cultivation of this field, keeping it open and growing, poses several problems. his paper 1 will focus on one of them, the criteria of evaluation. What means do we have to criticize artistic research: discuss, agree or disagree, on the quality and signiication of the research done?